The European Monetary System five years on: Achievements and prospects - Norbert Kleinheyer; Diethard B. Simmert (Intereconomics, 1984)
The record of the European Monetary System at the five-year mark is rather a disappointment for the System's advocates. Has the “EMS experiment” failed? Or is there potential for developing the System further to the advantage of all member countries?
Keywords: 330; Monetary Policy